Preservação do capital intelectual: uma proposta de gestão do conhecimento em uma instituição pública de ensino superior - Cogo, Moisés Pivetta (2017)
The purpose of this study was to develop a proposal to preserve intellectual capital and improve efficiency through the application of Knowledge Management in the context of a Federal University. In this sense, a quantitative research was carried out with employees at the Rectory of a public university, using the Knowledge Management Model for the Brazilian Public Administration (BATISTA, 2012), according to 7 criteria of analysis (Leadership in Knowledge Management, Processes, People, Technology, Knowledge Processes, Learning and Innovation, Results of the KM). Data were analyzed using Microsoft Office Excel 2007 and SPSS 20 software and presented through statistical analysis and KM maturity, represented by the sum of the final scores for each criterion. 257 employees participated in the survey, among them: 50,6% belong to the male gender; 55.8% are married; The mean age is 40.4 years; 72.7% have postgraduate schooling; 66.02% work in the institution for 10 years or less; 29.2% adhered to the process of flexibilization of working hours. Regarding the Criteria evaluated, the Knowledge Processes received the lowest score (2,545), with a total of 15,285; demonstrating that the respondents evaluated negatively the actions of identification, creation, storage, sharing and application of knowledge in the scope of work. On the other hand, the highest average found refers to the Technology Criterion (3,542), obtaining a higher score (21,252) among the Criteria, showing that the institution has a very developed technological base, acting in an appropriate manner regarding the actions that involve the infrastructure of information Technology. Overall, the respondents presented an average of 2.876, showing that the perception regarding knowledge management in the university is unsatisfactory. It should be noted that the lower performance in the Knowledge Processes Criterion shows a great challenge to be achieved in the institution that is the systematization of Knowledge Management in its work routines and processes. Based on this, it was verified that the institution reached a total of 120.75 points in the sum of the scores of the Criteria, fits the Initiation level, which demonstrates the begins to perceive and recognize the need to perform organizational knowledge management and its employees. In addition, among the respondents, the average perception of the current situation of Knowledge Management in UFSM was 5.42. As for the practices of knowledge sharing identified in the work sectors, the most important are the sharing of experiences; the dialogue and reflection among the employees to create new knowledge, among others factors. In general, there was no significant difference in the perception of the employees who joined the process of flexible working hours of those who did not join. Finally, a Proposal for a Knowledge Management Plan for the UFSM was elaborated, following methodology of Batista (2012), presenting the strengths and opportunities for improvement, developing a business case to highlight the relevance of Knowledge Management to institution and a Knowledge Management Plan.